Attachment of vimentin filaments to desmosomal plaques in human meningiomal cells and arachnoidal tissue (The Rockefeller University Press, 1984)
Desmosomal proteins are co-expressed with intermediate-sized filaments (IF) of the cytokeratin type in epithelial cells, and these IF are firmly attached to the desmosomal plaque. In meningiomal and certain arachnoidal cells, however, vimentin IF are attached to desmosomal plaques. Meningiomas obtained after surgery, arachnoid "membranes", and arachnoid granulations at autopsy, as well as meningiomal cells grown in short-term culture have been examined by single and double immunofluorescence and immunoelectron microscopy using antibodies to desmoplakins, vimentin, cytokeratins, glial filament protein, neurofilament protein, and procollagen. In addition, two-dimensional gel electrophoresis of the cytoskeletal proteins has been performed. Using all of these techniques, vimentin was the only IF protein that was detected in significant amounts. The junctions morphologically resembling desmosomes of epithelial cells have been identified as true desmosomes by antibodies specific for desmoplakins and they provided the membrane attachment sites for the vimentin IF. These findings show that anchorage of IF to the cell surface at desmosomal plaques is not restricted to cytokeratin IF as in epithelial cells and desmin IF as in cardiac myocytes, suggesting that binding to desmosomes and hemidesmosomes is a more common feature of IF organization. The co- expression of desmosomal proteins and IF of the vimentin type only defines a new class of cell ("desmofibrocyte") and may also provide an important histodiagnostic criterion.